ANALYSIS OF WOOD DUST LEVELS, NASAL MUCOCILIARY TRANSPORT RATE (NMTR) AND WORKERS’ RESPIRATORY COMPLAINTS IN FURNITURE HOME INDUSTRY, SURABAYA CITY, INDONESIA - Syarifa, Farach Dilla (International Journal of Psychosocial Rehabilitation, 2020)
Background:This research showed that wood dust in furniture workplace can potentially cause disruption to the nasal mucosa or slowing Nasal Mucociliary Transport Rate (NMTR). Research Objectives:Measuring wood dust levels in workplace, measuring the Nasal Mucociliary Transport Rate (NMTR) of the exposed and unexposed groups, and analyzing respiratory complaints and the use of PPE in the exposed group. Research Method:Cross sectional design, total sample size of the population amounted to 12 respondents containg 6 exposed and 6 unexposed respondents. Measurement of wood dust levels was done with EPAM 5000. Nasal Mucociliary Transport Rate (NMTR) test was done with Saccharin Test by ENT Specialists, using saccharin tablets and methylene blue tablets. Data analysis was obtained from cross tabulation results (crosstab). Research time was March to November 2019. Research Results:From the measurement of wood dust levels in areas was exposed 100% during operation and not exceeding the TLV of 5mg/m3, but the results got higher during the operation. The exposed group was 33.34% and the unexposed group was 8.33% in the abnormal category. The average Nasal Mucociliary Transport Rate (NMTR) of the exposed group was 11 minutes 57 seconds, while the average Nasal Mucociliary Transport Rate (NMTR) of the unexposed group was 7 minutes 11 seconds which showed the Nasal Mucociliary Transport Rate (NMTR) of the exposed group is slower than the unexposed group. Based on the cross tabulation of respiratory complaints showed that there was a relation between respiratory complaints Nasal Mucociliary Transport Rate (NMTR) status with contingency coefficient value of 0,549. Conclusions andRecommendations:The wood dust levels in the work environment of the exposed area exceeded the threshold value. The exposed group of Nasal Mucociliary Transport Rate (NMTR) was not normal or slower than the unexposed group. The exposed group that did not use PPE mask 100% of the time the Nasal Mucociliary Transport Rate (NMTR) was slow and categorized as abnormal, because it was above the threshold limit value which was more than 10 minutes 55 seconds. Suggestions for furniture workers, further increase of compliance to use PPE masks when working. Whereas for furniture owners pay more attention to workers in the use of PPE namely masks. Furniture owners can provide masks at work for their workers and socialize the importance of using masks when working.